KOMUNIKASI PEMERINTAH DESA DALAM PENGELOLAAN ALOKASI DANA DESA DI DESA TANA TORO KABUPATEN SIDENRENG RAPPANG - Surianah; Razak, Muhammad Rais Rahmat; Dema, Herman (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The aim of this research is to find out how the village government communicates in managing village fund allocation in Tana Tor Village in Sidenreng Rappang Regency. This research uses a qualitative description method. Data sources were obtained from observations, interviews and documentation. The data analysis techniques for this research are data reduction, data presentation and drawing conclusions. So the data that has been analyzed is then processed using Nvivo 12 plus. The research results show that village government communication in managing village fund allocation is still less effective. The factors inhibiting village government communication in managing village fund allocations are interference, interests and prejudice, in this case interference which has a high percentage of the other two factors.